Kapag ang palay naging bigas... may bumayo (Led Cinema Productions, 2002)
Lara Morena and Rose Valencia are sisters who are in love with the same man, JC Castro, for some reson is forced to marry Lara, the elder sister despite of his love for Rose. But later, JC and Rose cannot help but rekindle their old flame. soon, Lara finds out about the illicit affair and puts as end to the liaison as Brando Legaspi enters into the picture.